Malnutrition elevates delirium and ICU stay among critically ill older adult COVID-19 patients - Gholi, Zahra; Rezaei, Masoud; Vahdat Shariatpanahi, Zahra; Momen, Reza; Fallah Bagher Shaidaei, Mehdi; Gholami, Mostafa; Aghaee, Simin; Eskandari Sabzi, Hakimeh; Rajabi, Mohammad Reza (Frontiers in Medicine, 2024)
Background and aim: Malnutrition among intensive care unit (ICU) patients is associated with a higher risk of mortality and prolonged hospitalization. However, the influence of malnutrition on severe outcomes of ICU patients with coronavirus disease 2019 (COVID-19) is unclear. By evaluating the effect of malnutrition on the outcomes of COVID-19 in the ICU in elderly patients, this study will contribute to new knowledge of assessing the nutritional status and recovery of these patients.In the current single center prospective study, 310 critically ill COVID-19 patients with an age range of ≥65 years were recruited. Data on demographic characteristics, laboratory parameters, comorbidities, medications, and types of mechanical ventilation were collected in the first 24 hours of ICU admission. Malnutrition was defined based on the two-step approach of the Global Leadership Initiative on Malnutrition (GLIM) scale at baseline. During the 45 days after the baseline, we collected data on delirium incidence, mortality, invasive mechanical ventilation (IMV) requirement, length of ICU and hospital admission, and re-hospitalization.In this study, the prevalence of malnutrition was 63.4% among critically ill COVID-19 patients. During the 45-day follow-up, 190 (61.3%) COVID-19 deaths were recorded among the baseline 310 patients. After controlling for potential confounders, malnutrition was associated with an increased risk of delirium so malnourished COVID-19 patients had a significantly 35% higher risk of delirium than those without malnutrition (HR: 1.35, 95% CI: 1.01-1.83). Such a significant association was not for COVID-19 mortality and IMV requirement. In addition, malnutrition was associated with a significantly 84% greater odds of prolonged ICU admission (OR: 1.84, 95% CI:1.09-3.10). No significant association was seen between malnutrition and re-hospitalization and also prolonged hospital admission.Malnutrition was associated with an increased risk of delirium and prolonged ICU admission among critically ill elderly COVID-19 patients. Prevention, diagnosis, and treatment of malnutrition could be a key component in improving outcomes in these patients.